(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to know the role of rural bank in MSE economic development in Indonesia. The method used in this study uses regression The data used are secondary data obtained from bank publication reports during period 2018 - 2019. The population used in this study is rural banks in East Java and sample selection based on purposive sampling. The results showed that working capital loans from rural bank (BPR) have a significant effect on sales turnover, net profit margins and MSEs working capital turnoverThis research will be useful in knowing the performance of working capital disbursement to MSEs based on existing models based on existing parameters.